Conservative treatment of iatrogenic tracheal rupture (clinical case) - A. V. Sytov; P. V. Kononets; A. R. Shin; E. E. Budargin; V. E. Bugaev; I. Yu. Grishenkin (Вестник анестезиологии и реаниматологии, 2023)
The objective was to demonstrate a clinical case of iatrogenic injury of the trachea, which, despite its large size (length 65, width up to 25 mm), wastreated conservatively and, thus, avoided risks for the patient associated with the need for technically complex surgical intervention.Materials and methods. A 65-year-old patient diagnosed with peripheral cancer of the lower lobe of the left lung pT2aN0M0 stage IB, who routinely underwent thoracoscopic left lower lobectomy with mediastinal lymph node dissection. During anesthesia, tracheal intubation with a double-lumen tube of the R. Shaw type was carried out with technical difficulties; during intubation, a defect in the posterior wall of the trachea in its membranous part was formed. The defect was diagnosed on the first postoperative day.Results. Despite the large size of the tracheal defect, the patient had no symptoms of respiratory failure, and there were also no signs of mediastinitis or damage to the esophagus, which almost completely covered the resulting hole in the posterior wall of the trachea. Such circumstances made it possible to avoid a potentially dangerous and complex surgical intervention, carry out conservative therapy and wait for the resulting defect to heal through granulation tissue. Enhanced antimicrobial therapy was carried out; in order to sanitize the tracheobronchial tree and monitor healing, fiber-optic bronchoscopy was performed, which made it possible to clearly demonstrate both the damage itself and the stages of its healing.Conclusions. The described case clearly demonstrates the potential for healing of even very extensive tracheal wall defects with conservative therapy. However, it is important to note that success in this clinical case was the result of a combination of circumstances – only the membranous part of the trachea was damaged; the defect was almost completely covered by the intact esophagus, which reduced the risk of developing mediastinitis and prevented the development of severe pneumomediastinum and subcutaneous emphysema. There were no signs of respiratory failure. The patient was transferred from the intensive care unit on the 13th day of the postoperative period, discharged from the hospital on the 22nd day.